Contribuições das unidades de auditorias das universidades federais brasileiras para os indicadores de impacto social - Contarin, Jaqueline (2023)
Brazilian Federal Universities (UFs) contribute to the country’s political, economic, cultural, and social development, through education, research, outreach, and innovation. In this context, measuring results, mitigating risks, and improving work processes in universities are key to the success of their institutional projects and to the impact on society’s sustainable development. The main goal of this work was to research the contribution of Brazilian UF audit units to the improvement of their social indicators, based on the 17 Sustainable Development Goals (SDGs), implemented by the United Nations, and incorporated by the Times Higher Education (THE) university ranking. The method used was document analysis, with a mixed quantitativequalitative approach. The sample analyzed included 286 audit reports from 2019 to 2020, retrieved from the institutional websites of 33 UFs. The results comprise a set of indicators that characterize the activities of UF audit units and identify the relationship between the audit units’ recommendations and their contribution to the development and improvement of the UFs’ social indicators. The theoretical discussion and obtained results are expected to contribute to the research on the role of universities and their social impact through the development of social indicators, while using the relationship between recommendations from audit units and the respective areas in the social indicators.